Dyspneia, general health, and voice in Chronic Obstructive Pulmonary Disease (Research, Society and Development, 2021)
Introduction: The chronic irreversible and progressive airflow limitation that occurs in Chronic Obstructive Pulmonary Disease (COPD) may impair breathing, and harm one’s general health and voice. Objective: To verify the correlation between degree and impact of the disease on the general health status of individuals with COPD, their dyspnea sensation and voice-related quality of life. Methods: The sample consisted of a group of 37 subjects diagnosed with COPD, of both sexes, aged between 35 and 89 years. Modified Medical Research Council scale (mMRC), COPD Assessment Test (CAT), Voice-Related Quality of Life questionnaire, and determination of the severity of the disease by limiting airflow according to the Global Initiative for Chronic Obstructive Lung Disease (GOLD) were performed. Results: Most of the individuals showed disease grade and CAT results as moderate to severe; mMRC from 1 to 3; total and physical domain scores below the cutoff point for the Voice-Related Quality of Life. There was a significant inverse correlation between total/physical domain scores of V-RQOL and CAT. Conclusions: The subjects with COPD were homogeneously distributed between the sexes, were older, and presented an impact of the disease on general health and sensation of dyspnea in moderate and severe degrees. Voice-Related Quality of Life was below the cutoff point. We found that the worse the results of the Voice-Related Quality of Life questionnaire, the greater the impact of the symptoms of chronic obstructive pulmonary disease on the general health status.